Long-Term Outcome of Autotransplantation of a Complete Root Formed a Mandibular Third Molar - Hiroyuki Kimura; Yusuke Hamada; Taro Eida; Tsuyoshi Kumano; Kazutoshi Okamura; Makoto Yokota (Hindawi Limited, 2021)
Autogenous tooth transplantation is a procedure to reposition an autogenous tooth to another extraction area or surgically created recipient site. The autotransplantation procedures have been documented well in the literature, and the survival rate of the transplanted teeth was reported to be more than 90% after ten years. Therefore, autotransplantation might have been overlooked as a treatment option. The purpose of this case report is to evaluate the long-term (29-year) success and periodontal stability of the tooth autotransplantation from the mandibular third molar to the second molar. A 24-year old female presented to a clinic with a large caries lesion with periapical radiolucnecy on to tooth #18. The tooth was extracted with the site and treated with autogenous tooth transplantation from #17 with a complete root form. Endodontic treatment was completed 3 months post autotransplantation; the final prosthesis was placed 6 months postoperatively. The patient has shown excellent oral hygiene care and high compliance with the regular maintenance recall program. The transplanted tooth has been still functioning without any symptoms. Radiographic and clinical examinations revealed stable periodontal and endodontic conditions over the 29 years after the procedure. This case report showed the long-term success of autotransplantation of the mandibular third molar with a closed root apex to the second molar site. Autotransplantation can be an option when an adequate donor site is available to reconstruct the occlusion after the tooth extraction.